CONSIDERATIONS ON A COMPARATIVE APROACH REGARDING WHEAT AND CORN CROPS IN THE TRANSYLVANIAN PLAIN - Andra Porutiu; Felix Arion; Iulia Muresan; Camelia Oroian; Tudor Salagean; Raluca Farcas (Agricultura, 2016)
The goal of this research is to exhibit the differentiated fertilization systems involved in obtaining high productions for wheat (grown following soy) and corn crops in the reference area. In this study it was tracked the effect of the nitrogen-phosphorous interaction in achieving the wheat and corn productions. The research presents the stated results as annual (partial) values and it will continue with them as being reference values for further experimental years (as stages in long term experiments).